HUBUNGAN KINERJA KADER POSYANDU LANSIA DENGAN MOTIVASI LANSIA MENGUNJUNGI POSYANDU LANSIA - Darmanto, Jendri '; ', Arneli wati; ', Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research is to identify the reationship between cadre performance of elderly posyandu and elder motivation to visit Elderly Posyandu. Research method used in this research is corellation descriptive with cross sectional design. This research was conducted in the Technical Implementing Service Mangement Department (UPTD) health clinic of Koto Baru, Singingi district Kuantan Singing Regency. Sampling method used in this research was proposive sampling. The measuring instrument was a questionnaire which has tested validity and reliability. Analysis methods used were univariate and bivariate with Chi-Square test. The result of Chi-Square test was, p value = 0.209, showed that p value > α 0.05, therefore it can be concluded that Ho is rejected, so then the researcher can summed up that there is no relationship between cadre performance of elderly posyandu and elder motivation to visit elderly posyandu. The result of this research is expected that it can be an input to any relevant institutions, particularly The UPTD health clinic of Koto Baru to plan programmes to raise awareness on the urgency of elderly posyandu for elders as health services to undertake health examination, such as mental status, nutrition satus, and physical health on a regular basis, so then it can be detected early in case of there is health problem.   Key words : Cadre Performance of Elderly Posyandu, Elder Motivation